The relationship and taxonomic position of the genera Apolophus and Scolomus (Hymenoptera: Ichneumonidae) - Gauld, Ian D.; Wahl, David B. (Zootaxa, 2006)
The metopiine genus Apolophus Townes is treated as a junior synonym [syn. nov.] of the ctenopelmatine genus Scolomus Townes & Townes. The distinguishing features of the expanded genus are described and illustrated. The systematic position of Scolomus is discussed and it is concluded that the genus belongs to the Metopiinae. The monophyly of the Ctenopelmatinae is open to question and it is suggested that the Metopiinae may have arisen from within the Ctenopelmatinae.